Impact of Syndecan-2-Selected Mesenchymal Stromal Cells on the Early Onset of Diabetic Cardiomyopathy in Diabetic db/db Mice - Pappritz, Kathleen; Dong, Fengquan; Miteva, Kapka; Kovacs, Arpad; El-Shafeey, Muhammad; Kerim, Bahtiyar; O'Flynn, Lisa; Elliman, Stephen Joseph; O'Brien, Timothy; Hamdani, Nazha; Tschöpe, Carsten; Van Linthout, Sophie (Frontiers in Cardiovascular Medicine, 2021)
Background: Mesenchymal stromal cells (MSCs) are an attractive cell type for cell therapy given their immunomodulatory, anti-fibrotic, and endothelial-protective features. The heparin sulfate proteoglycan, syndecan-2/CD362, has been identified as a functional marker for MSC isolation, allowing one to obtain a homogeneous cell product that meets regulatory requirements for clinical use. We previously assessed the impact of wild-type (WT), CD362−, and CD362+ MSCs on local changes in protein distribution in left ventricular (LV) tissue and on LV function in an experimental model of early-onset diabetic cardiomyopathy. The present study aimed to further explore their impact on mechanisms underlying diastolic dysfunction in this model. Materials: For this purpose, 1 × 106 WT, CD362−, or CD362+ MSCs were intravenously (i.v.) injected into 20-week-old diabetic BKS.Cg-m+/+Leprdb/BomTac, i.e., db/db mice. Control animals (db+/db) were injected with the equivalent volume of phosphate-buffered saline (PBS) alone. After 4 weeks, mice were sacrificed for further analysis. Results: Treatment with all three MSC populations had no impact on blood glucose levels in db/db mice. WT, CD362−, and CD362+ MSC application restored LV nitric oxide (NO) and cyclic guanosine monophosphate (cGMP) levels in db/db mice, which correlated with a reduction in cardiomyocyte stiffness. Furthermore, all stromal cells were able to increase arteriole density in db/db mice. The effect of CD362+ MSCs on NO and cGMP levels, cardiomyocyte stiffness, and arteriole density was less pronounced than in mice treated with WT or CD362− MSCs. Analysis of collagen I and III protein expression revealed that fibrosis had not yet developed at this stage of experimental diabetic cardiomyopathy. All MSCs reduced the number of cardiac CD3+ and CD68+ cells in db/db mice, whereas only splenocytes from CD362−- and CD362+-db/db mice exhibited a lower pro-fibrotic potential compared to splenocytes from db/db mice. Conclusion: CD362+ MSC application decreased cardiomyocyte stiffness, increased myocardial NO and cGMP levels, and increased arteriole density, although to a lesser extent than WT and CD362− MSCs in an experimental model of early-onset diabetic cardiomyopathy without cardiac fibrosis. These findings suggest that the degree in improvement of cardiomyocyte stiffness following CD362+ MSC application was insufficient to improve diastolic function.